Rheological behavior of Peruvian carrot starch gels as affected by temperature and concentration - Albano, Kivia M. [UNESP]; Franco, Celia M. L. [UNESP]; Telis, Vania R. N. [UNESP] (Elsevier B.V., 2014)
Beyond their nutritional importance, starches present a relevant technological role in processed foods. The gelatinization process that occurs during heating of starch suspensions is generally followed by considerable shearing rates, which affects the rheological behavior. This work investigated the rheology of gels produced from Peruvian carrot (Arracacia xanthorrhiza B.) starch at different concentrations (2, 6, and 10%) and temperatures (10, 30, 50 and 70 degrees C), using rheological measurements under steady and oscillatory shear. In addition, the system microstructure was analyzed by optical microscopy around the gelatinization temperature (59.5-61 degrees C). The gels exhibited shear thinning behavior and high thixotropy. Power Law was fitted to flow curves and the consistency index was affected by temperature and starch concentration. Steady and oscillatory shear measurements showed that the rheological behavior was highly dependent on the fraction of gelatinized starch granules, which in turn was affected by water availability and temperature. Depending on temperature and concentration, Peruvian carrot starch resulted in more viscous or more elastic systems, which could be applied in different gel-like foods. Its low gelatinization temperature contributes to easy cooking and high digestibility, but technological applications must take into account its high susceptibility to intense shearing. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Apparent viscosity; Viscoelasticity; Gelatinization; Arracacia xanthorrhiza B